Optimization Of Material Transportation Assignment For Automated Guided Vehicle (AGV) System - Mohamad, Nor Rashidah; Md Fauadi, Muhammad Hafidz Fazli; Zainudin, Siti Fairus; Mohamed Noor, Ahamad Zaki; Jafar, Fairul Azni; Mat Ali, Mahasan (Science Publishing Corporation, 2018)
This article focuses on Material Transportation Assignment problem that is identified as an Automated Guided Vehicles (AGV) multi-load task assignment. The primary goal of this paper is to determine the factors needed to optimize material transportation system. This study also explores the optimization and performance enhancement of the Flexible Manufacturing System (FMS) environment. The implementation of Genetic Algorithm (GA) in this model is to obtain the optimal solution for FMS layout. The combination of delivery and pickup task are addressed by modified algorithm for advancement in multiple loads AGV. The result obtained depicts that the proposed task assignment method with a modified genetic algorithm can produce acceptable performance compared to conventional task assignment method.